THE STUDY OF THE STRUCTURE OF MANY BALL-REDUCING COATING WHICH IS APPLIED GASOMETRICAL SPRAY - Artemchuk, V. V. (Science and Transport Progress, 2007)
The article considers the questions connected with research of the structure of multi-layered coverings. A restoring coating was applied on the worn-out surface by a gas-thermal method. In the course of such treatment a layer of soft metal is applied first, being necessary for improvement of the covering coupling with the basis, then the following layers, carrying out the working functions, are laid. The problem of increasing adhesion with combination of the necessary functions is being thus solved.